The Ayala museum an adaptive reuse of existing facilities - Garcia, Anna Ma. Luisa T.; Florendo Raquel B. (1989.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman
Keywords: Museums -- Philippines; Ayala Museum